Rheological properties and structural features of coconut milk emulsions stabilized with maize kernels and starch. (November 2019) - Lu, Xu; Su, Han; Guo, Juanjuan; Tu, Jinjin; Lei, Yi; Zeng, Shaoxiao; Chen, Yingtong; Miao, Song; Zheng, Baodong
Abstract: In this study, maize kernels and starch with different amylose contents at the same concentration were added to coconut milk. The nonionic composite surfactants were used to prepare various types of coconut milk beverages with optimal stability, and their fluid properties were studied. The steady and dynamic rheological property tests show that the loss modulus ( G″ ) of coconut milk is larger than the storage modulus ( G′ ), which is suitable for the pseudoplastic fluid model and has a shear thinning effect. As the droplet size of the coconut milk fluid changed by the addition of maize kernels and starch, the color intensity, ζ -potential, interfacial tension and stability of the sample significantly improved. The addition of the maize kernels significantly reduced the size of the droplets ( p  < 0.05). The potential values of zeta ( ζ ) and the surface tension of the coconut milk increased. Based on the differential scanning calorimetry (DSC) measurement, the addition of maize kernels leads to an increase in the transition temperature, especially in samples with a high amylose content. The higher transition temperature can be attributed to the formation of some starches and lipids and the partial denaturation of proteins in coconut milk, but phase separation occurs. These results may be helpful for determining the properties of maize kernels in food-containing emulsions (such as sauces, condiments, and beverages) that achieve the goal of physical stability. Graphical abstract: Image 103 Highlights: The amylose content increased the viscosity and yield stress of coconut milk. The coconut milk fluid of the maize kernel is similar to high-amylose maize starch. The addition of corn improves the stability of coconut milk.